Affordance dalam desain antarmuka pengguna: studi kasus pada baby boomers pengguna Tokopedia - Virginia, Fergie (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
Tokopedia is one of the companies in Indonesia that has a unicorn status. With a vision to build a platform that allows anyone to start and find anything and anywhere, Tokopedia also supports Micro, Small and Medium Enterprises (MSMEs) and individuals to develop their businesses through application. Even so, this does not guarantee that all Tokopedia users can really easily use the application. The baby boomer generation is a generation that faces more difficulties in processing new or complex information, thus affecting their learning about new technologies, including the user interface design of an application. The purpose of this study is to understand how the user interface elements are applied to the Tokopedia application and how the baby boomer affordance to the Tokopedia application user interface design. The method used is a case study with a qualitative approach. The results show that the user interface design elements of the Tokopedia application in the perception of baby boomer generation are always related to design elements, use of color, and layout. Some of these elements have been understood by the user's function. Nevertheless, there are some technical things, such as the use of free space, that users still don't understand. Thus, Tokopedia still has to make some improvements to the application's user interface design.